1981
DOI: 10.1111/j.1365-2621.1981.tb14570.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Scores and Shear Force Values for Beef Roasts Cooked Either Before or After Chilling

Abstract: Sensory and physical characteristics were determined on beef semimembranosus and semitendinosus muscles removed and cooked either 1.5 hr post-exsanguination or after 7 days of chilling by either steam, hot water vat or convectional electric cookery. The effects of cookery method on sensory and physical characteristics were not statistically significant (P>O.Ol). Hot-boned roasts from both muscles served as cubes had higher shear force values, higher amounts of connective tissue (sensory panel), and lower tende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1981
1981
1985
1985

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…The lower (P < 0.05) WCA for electrically stimulated, HB chops indicated the tenderness advantage of electrical stimulation used in conjunction with hot-boning. A decrease in tenderness of hot-boned meat has been reported by several authors (Gilbert and Davey, 1976;Cross et al, 1979;Ray et al, 1980aRay et al, , 1983Berry et al, 1981;Griffin et al, 1981;Lyon et al, 1983). On the contrary, McLeod et al (1973) reported that cooked, hot-boned lamb legs were more tender than cooked, cold-boned lamb legs.…”
Section: Electrical Stimulation By Treatmentmentioning
confidence: 76%
“…The lower (P < 0.05) WCA for electrically stimulated, HB chops indicated the tenderness advantage of electrical stimulation used in conjunction with hot-boning. A decrease in tenderness of hot-boned meat has been reported by several authors (Gilbert and Davey, 1976;Cross et al, 1979;Ray et al, 1980aRay et al, , 1983Berry et al, 1981;Griffin et al, 1981;Lyon et al, 1983). On the contrary, McLeod et al (1973) reported that cooked, hot-boned lamb legs were more tender than cooked, cold-boned lamb legs.…”
Section: Electrical Stimulation By Treatmentmentioning
confidence: 76%
“…Tenderness of the pre-rigor (cooked within 20 min postexcision) roasts (SM and ST) was greatly enhanced with the low temperature, long duration cooking (Tables 6 and 7). Other studies (Weiner et al, 1966;Montgomery et al, 1977;Ray et al, 1980Ray et al, , 1982Griffin et al, 1981;Berry et al, 1981) have reported decreased tenderness of pre-rigor cooked roasts when compared with their CB counterparts. However, Cia and Marsh (1976) found that microwave cooking improved the tenderness of pre-rigor muscles compared with boiling.…”
Section: Tenderness Evaluationmentioning
confidence: 95%
“…Shortening during cooking for the HB, ST was greater than for the HB, SM roasts and may have resulted in reduced tenderness for the HB, ST roasts. The slow, low temperature cooking may have permitted the muscle to have less severe rigor development during cooking, rather than the more severe rigor induced by subjecting the muscle to an initial high cooking temperature (68OC), as was done in earlier studies (Ray et al, 1980(Ray et al, , 1982Berry et al, 1981;Griffin et al, 1981). Cooking time and cooking losses were reduced (P < 0.05) for HB, ST and SM roasts when compared with their CB counterparts in this study.…”
Section: Conclusion Low Temperature-longmentioning
confidence: 99%
See 2 more Smart Citations